Differences in Heart Graft Survival by Recipient Sex. Issue 10 (October 2021) - Foster, Bethany J.; Zhang, Xun; De Simone, Alexia; Dahhou, Mourad; Sapir-Pichhadze, Ruth; Cardinal, Heloise; West, Lori
Abstract : Background: We aimed to characterize patterns of differences in heart graft failure rates by recipient sex, accounting for modifying effects of donor sex and recipient age. Methods: We evaluated 69 246 first heart transplant recipients (1988–2019; Scientific Registry of Transplant Recipients). We used multivariable time-varying Cox models, considering recipient sex by donor sex by recipient age interaction and adjusting for potential confounders. Using the hazard ratio (HR) from the models and a fixed profile of recipient and donor characteristics, we also compared fitted absolute failure rates by recipient sex. Results: Among recipients of male donors, female recipients of all ages had higher failure rates than males (0–12 y: HR 1.36 (95% confidence interval [CI], 1.03-1.81); 13–24 y: 1.43 [1.09-1.88]; 25–44 y: 1.22 [0.95-1.57]; ≥45 y: 1.16 [1.06-1.27]); differences were statistically significant in all age intervals except 25–44 y. When the donor was male, 13 to 24-y-olds showed the largest absolute difference in fitted absolute failure rates, with rates higher by 11.3 failures per 1000 person-y in female than male recipients. Among recipients of female donors, there were no statistically significant differences in graft failure rates between female and male heart recipients of any age. Although point estimates suggested higher failure rates in female than male recipients <25 y (0–12 y: HR 1.19 [95% CI, 0.85-1.66]; 13–24 y: 1.17 [0.84-1.63]), these were not statistically significant. Conclusions: Female recipients tended to have poorer outcomes than males, particularly at younger ages and when the donor was male, consistent with observations in kidney transplants. Abstract : Supplemental Digital Content is available in the text.